Implementation of the Muqassam Memorization Method in Nature Improving Memorization of Nushus Santri Class II Regular A TMI Al-Amien Prenduan Material for the 2023 Academic Year - Ahmad Barisi; Achmad Maulidi (Penerbit Hellow Pustaka, 2024)
The problem raised in this research is how to improve the nushus memorization of class II Regular A students using the muqassam memorization method, whereas the nushus memorized is quite long, so special methods are needed to make the memorization process easier. One method that can be used is the Muqassam memorization method, the muqassam method is a divided memorization method, the steps in this method are to divide the memorization into several parts and memorize them sequentially. The memorization activity is carried out continuously until it is completely memorized. This is used to improve the memorization of class II Regular A students. This research uses a qualitative case study approach. Data sources were obtained from teachers and several students of class II Regular A. The data collection methods used were observation, interviews and documentation. Data analysis is carried out by reducing data, presenting data, and drawing conclusions. Meanwhile, the technique used to check the validity of the data is technical triangulation. The results of this research are that the application of the muqassam memorization method can increase the memorization of nushus of students in class II Regular A. One form of increasing memorization in students in class II Regular A includes the number of students who have memorized their notes increasing, it can also be seen from the ability of the students in answering the questions asked. usually given before starting new material with the aim of repeating the material studied in the previous week. This increase is one form of increasing nushus memorization of class II Regular A students after applying the muqassam memorization method in nushus learning.